Ozone combined with doxorubicin exerts cytotoxic and anticancer effects on Luminal-A subtype human breast cancer cell line - Karagulle,Onur Olgac (2022)
SUMMARY OBJECTIVE: We aimed to examine the potential anticancer effects of ozone applied after chemotherapeutic treatment with different concentrations of doxorubicin in Luminal-A subtype of human breast cancer cell line (MCF-7) and compare the results with effects on L929 fibroblast cell line. METHODS: Both cell lines were incubated with increasing doses of doxorubicin (1–50 μM) for 24 h at 37°C. Then, half of groups were incubated with 30 μg/mL ozone for 25 min as combination groups. Cell viability was analyzed by MTT assay, apoptosis by flow cytometry, and levels of tumor necrosis factor alpha, transforming growth factor beta, and matrix metalloproteinase-2 and MMP-9 by immunocytochemistry. RESULTS: Doxorubicin + ozone treatment enhanced viability of L929 (p<0.01) but reduced viability of MCF-7 compared to only doxorubicin-applied cells without ozone treatment (p<0.001). This combined treatment also enhanced apoptotic effect of doxorubicin on MCF-cells (p<0.001), but not on L929. It significantly increased all protein levels of L929 compared with those of other groups (p<0.05 for tumor necrosis factor alpha and MMP-2; p<0.01 for transforming growth factor beta and MMP-9). This treatment reversed the effect of doxorubicin on tumor necrosis factor alpha levels and considerably reduced MMP-2 and MMP-9 levels of MCF-7 compared with those of control group (p<0.01 and p<0.001, respectively). CONCLUSION: Ozone treatment potentiated the apoptotic and anticancer activities of doxorubicin in MCF-7 cells and showed repairing and healing effect on healthy fibroblast cells, which were damaged from cytotoxic effects of chemotherapeutic agent. MCF-7 cells may acquire sensitivity against the doxorubicin combined with ozone treatment through activating tumor necrosis factor alpha, MMP-2, and MMP-9 expressions.